Analisis Konsistensi Nahdlatul Ulama (NU) Mendorong Kemerdekaan Palestina - E. Ervi Siti Zahroh Zidni (ISLAM NUSANTARA:Journal for the Study of Islamic History and Culture, 2023)
Since the beginning, The Nahdlatul Ulama (NU), as organization has had an important international role in promoting freedom of thought, as demonstrated by the establishment of the Hijaz committee. NU has continued to engage in the global arena, particularly in its support for Palestinian independence. Despite the fact that not all Palestinians are Muslim, religion has been a contributing factor in NU's unwavering support for Palestine. However, there are other dominant factors that have solidified NU's position on this issue, which are explored in this article through qualitative research methods and descriptive analysis of relevant literature and documents. The study examines NU's consistency in supporting Palestinian independence and the attitudes of four NU leaders, namely Abdurrahman Wahid, Hasyim Muzadi, Said Aqiel Siraj, and Yahya Cholil Tsaquf. Although all four leaders support Palestinian independence, their reasons and backgrounds differ, resulting in some controversy and differing mindsets within NU, Indonesian society, and even Arab embassies in Indonesia. The article argues that these differences can be attributed to variations in domestic political conditions that the leaders faced, which influenced their approaches to defending and supporting Palestine. External factors such as diplomatic relationships and non-state actors also played a role in shaping NU's stance on this issue.